Major- and trace-element compositions of indicator minerals that occur as macro- and megacrysts, and of xenoliths, from kimberlites in Northeastern Angola - Robles Cruz, Sandra E. (2012)
In this study, we compare the major- and trace-element compositions of olivine, garnet, and clinopyroxene that occur as single crystals (142 grains), with those derived from xenoliths (51 samples) from six kimberlites in the Lucapa area, northeastern Angola: Tchiuzo, Anomaly 116, Catoca, Alto Cuilo-4, Alto Cuilo-63 and Cucumbi-79. The samples were analyzed using electron probe microanalysis (EPMA) and laser-ablation inductively coupled plasma-mass spectrometry (LA-ICP-MS). The results suggest different paragenetic associations for these kimberlites in the Lucapa area. Compositional overlap in some of the macrocryst and mantle xenolith samples indicates a xenocrystic origin for some of those macrocrysts. The presence of mantle xenocrysts suggests the possibility of finding diamond. Geothermobarometric calculations were carried out using EPMA data from xenoliths by applying the program PTEXL.XLT. Additional well calibrated single-clinopyroxene thermobarometric calculations were also applied. Results indicate the underlying mantle experienced different equilibration conditions. Subsequent metasomatic enrichment events also support a hypothesis of different sources for the kimberlites. These findings contribute to a better understanding of the petrogenetic evolution of the kimberlites in northeastern Angola and have important implications for diamond exploration.